Pengembangan Modul Membuat Pola dengan Teknik Konstruksi pada program Pelatihan Keliling (Mobile Training Unit) - Parinem, Parinem (Media Manajemen Pendidikan, 2024)
Making training module using Construction Techniques that is adequate for use in the Mobile Training Unit, test the feasibility of developing the module, and determine user perceptions of the module. This research is development research by adapting the ADDIE model. This development model consists of five development stages, namely: Analysis, Design, Development, Implementation, and Evaluation. Product feasibility assessments are carried out by media experts and material experts. Data collection methods were carried out by interviews, observation and questionnaires. The trial subjects were Mobile Training Unit (MTU) training participants in Bantul, Sleman and Yogyakarta organized by BLKPP DIY. The data analysis technique uses qualitative analysis techniques from interviews with sources and qualitative analysis of the assessment scores of media experts, material experts and users (instructors and training participants). This research produces a product in the form of a material book on Making Patterns with Construction Techniques which can be used as teaching material in basic sewing lessons for the Mobile Training program. The feasibility of the module based on the media expert's assessment and the material expert's assessment included in the "very feasible" criteria. User perception based on the instructor's assessment and the training participants' assessment including the "good" criteria.